(untitled) (Research, Society and Development, 2021)
Objective: To conduct a literature review to identify which drugs cause the most drug induced liver injury (DILI) in hospitalized patients. Methodology: A literature review was performed through a systematic search for articles on DILI in hospitalized patients. This research followed the PRISMA-P (Main Items for Reporting Systematic Reviews and Meta-Analyses) recommendation and the following electronic databases were searched: PubMed (National Library of Medicine, National Institutes of Health), Web of Science, Scopus and Lilacs (Latin American and Caribbean Literature in Health Sciences). Results: Initially, a total of 454 articles were identified and after reviewing the full text, 27 articles were selected. All articles considered the value of the liver enzyme alanine aminotransferase increased for DILI characterization. Reports of a wide variety of medications, as probable causes of DILI, were identified in hospitalized patients. Conclusion: Among the reports of drugs found associated with DILI, those with the most frequent occurrence, according to the ATC classification, were: 85% (23) of drugs in J group, 37% (10) in M group, 33.3% (9) in N group and 33.3% (9) in C group. The J group, which covers anti-infective drugs, had the highest number of reports, with 47.8% (11) of antibiotics, 47.8% (11) of antituberculostatics and 34.7% (8) of antifungals. Beta-lactams group, especially Amoxacillin-Clavulanate, Rifampicin, Isoniazid, Pyrazinamide and Fluconazole were stood out.